Case Report: Androgen receptor-positive, locoregionally advanced breast cancer in a transgender man and an update on breast cancer management in a gender-diverse patient population - Ramdas, Yastira; Reinicke, Trenton; Schnurr, Carolyn A.; Nadeau, Laura; Zakalik, Dana; Lahiri, Sharon W.; Brudvik, Andrea; Kiran, Sayee; Busuito, Christina M.; Dilworth, Joshua T. (Frontiers in Oncology, 2025)
The role of androgen receptor (AR) signaling in breast cancer is underexplored and may be particularly important in the treatment of patients with higher levels of circulating androgens. We discuss the management of a 70-year-old, postmenopausal transgender man with a six-and-one-half-year history of testosterone therapy, who presented with locoregionally advanced, invasive lobular carcinoma with apocrine features that was estrogen receptor (ER)-negative, progesterone receptor (PR)-negative, human epidermal growth factor receptor 2 (HER2)-positive, and AR-positive. The approach to discontinue his testosterone indefinitely upon diagnosis was determined through shared-decision making with the patient. He received neoadjuvant HER2-directed chemotherapy and achieved a complete metabolic response. He underwent bilateral total mastectomies with left targeted axillary lymph node dissection. Final pathology showed a near complete pathologic response in the breast and a pathologic complete response in three sentinel lymph nodes. He completed a course of conventionally fractionated left chest wall and regional nodal proton beam irradiation and received adjuvant HER-2 directed therapy. He tolerated treatment well and remains disease-free two years since diagnosis. This case report and review underscore the importance of a multi-disciplinary and nuanced approach to personalized management of breast cancer in a gender-diverse patient population. Continued characterization of the AR as a potential therapeutic target in patients with breast cancer is warranted